Small molecule targeting CELF1 RNA-binding activity to control HSC activation and liver fibrosis. Issue 5 (2nd March 2022) - Tan, Yang; Sun, Xueqing; Xu, Yizhu; Tang, Bingjie; Xu, Shuaiqi; Lu, Dong; Ye, Yan; Luo, Xiaomin; Diao, Xu; Li, Fulong; Wang, Tianyi; Chen, Jiayu; et al.
Abstract: CUGBP Elav-like family member 1 (CELF1), an RNA-binding protein (RBP), plays important roles in the pathogenesis of diseases such as myotonic dystrophy, liver fibrosis and cancers. However, targeting CELF1 is still a challenge, as RBPs are considered largely undruggable. Here, we discovered that compound 27 disrupted CELF1-RNA binding via structure-based virtual screening and biochemical assays. Compound 27 binds directly to CELF1 and competes with RNA for binding to CELF1. Compound 27 promotes IFN-γ secretion and suppresses TGF-β1-induced hepatic stellate cell (HSC) activation by inhibiting CELF1-mediated IFN-γ mRNA decay. In vivo, compound 27 attenuates CCl4 -induced murine liver fibrosis. Furthermore, the structure-activity relationship analysis was performed and compound 841, a derivative of compound 27, was identified as a selective CELF1 inhibitor. In conclusion, targeting CELF1 RNA-binding activity with small molecules was achieved, which provides a novel strategy for treating liver fibrosis and other CELF1-mediated diseases.